Fabrice Flipo, Nature et politique: contribution à une anthropologie de la modernité et de la globalisation - Gervais, Mathieu (Analéctica, 2023)
Fabrice Flipo deplores the lack of recognition of ecology in the French intellectual field, in particular that of political philosophy. According to him, this situation is linked to the imbalance that exists between, on the one hand, the numerous and scientifically constructed critics of ecological theory and, on the other hand, the insufficiency of the answers which one brings to them. Therefore, by taking the criticisms made seriously, he tries to provide them with a philosophically sound answer. This starting point justifies the division of his book into four main chapters, each structured around a controversy, an accusation made with regard to ecology: 1) the accusation of antihumanism, 2) the accusation of anti-democracy, 3) returns the ecology either to liberalism or to Marxism, 4) the accusation of anti-modernism because of "re-enchantment". These chapters are dense and mobilize numerous references. This has the advantage of providing a welcome synthesis of all the concepts related to ecological issues and of placing them in an often poorly understood philosophical context, so we can also read this book as an introduction to political ecology. DOI: 10.5281/zenodo.3905257